Functional Modifications Induced via X‐ray Nanopatterning in TiO2 Rutile Single Crystals. Issue 10 (15th September 2021) - Alessio, Andrea; Bonino, Valentina; Heisig, Thomas; Picollo, Federico; Torsello, Daniele; Mino, Lorenzo; Martinez-Criado, Gema; Dittmann, Regina; Truccato, Marco
Abstract : The possibility to directly write electrically conducting channels in a desired position in rutile TiO2 devices equipped with asymmetric electrodes—like in memristive devices—by means of the X‐ray nanopatterning (XNP) technique (i.e., intense, localized irradiation exploiting an X‐ray nanobeam) is investigated. Device characterization is carried out by means of a multitechnique approach involving X‐ray fluorescence (XRF), X‐ray excited optical luminescence (XEOL), electrical transport, and atomic force microscopy (AFM) techniques. It is shown that the device conductivity increases and the rectifying effect of the Pt/TiO2 Schottky barrier decreases after irradiation with doses of the order of 10 11 Gy and fluences of the order of 10 12 J m −2 . Irradiated regions also show the ability to pin and guide the electroforming process between the electrodes. Indications are that XNP should be able to promote the local formation of oxygen vacancies. This effect could lead to a more deterministic implementation of electroforming, being of interest for production of memristive devices. Abstract : The electrical modifications induced by intense X‐ray nanobeams on rutile TiO2 are investigated. A multitechnique approach involving X‐ray fluorescence (XRF), X‐ray excited optical luminescence (XEOL), atomic force microscopy (AFM), and electrical characterization shows that high‐dose X‐ray irradiations of TiO2 memristive‐like devices are able to pin and guide the electroforming process in these devices.